Descemet Membrane Endothelial Keratoplasty (DMEK) for Severe Verrucous Posterior Polymorphous Corneal Dystrophy with Uncommon Clinical and Ultrastructural Findings - Berger, Tim; Seitz, Berthold; Löw, Ursula; Flockerzi, Fidelis; Schlötzer-Schrehardt, Ursula; Daas, Loay (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose To report a case of severe verrucous posterior polymorphous corneal dystrophy (PPCD) and cataract, which was treated with Descemet membrane endothelial keratoplasty (DMEK) and simultaneous cataract surgery as a triple procedure (Triple-DMEK).Methods A 62-year-old female patient presented to our department for co-evaluation of advanced PPCD with cataract and progressive light sensitivity in both eyes. The clinical examination demonstrated unusual clinical findings with prominent verrucous lesions on the posterior surface of the cornea without corneal decompensation. We performed a Triple-DMEK in case of simultaneous cataract. The corneal tissue was examined by light and transmission electron microscopy.Results Intraoperatively, it was difficult to remove the verrucous structures completely after classical descemetorhexis. Light microscopic examination demonstrated epithelium-like transformation of the corneal endothelium by immunostaining (cytokeratin AE1/3 staining). Transmission electron microscopy revealed thickening of Descemetʼs membrane (18.5 to 30.0 µm). The anterior banded layer had a normal structure and was slightly thickened (3.5 to 5.5 µm). A normal posterior non-banded layer (PNBL) was observed but thinned (2.5 to 4.0 µm) or missing. It was followed by an altered PNBL with abnormal fibrillary inclusions, which was strongly and variably thickened (11.0 to 24.5 µm). The corneal endothelium was degenerated, partially absent, and epithelial-like altered. The nodular lesions were found to consist of a few degenerated cells that were embedded in an amorphous extracellular matrix interspersed with collagen fibers, which were not arranged in regular lamellae, forming the corneal stroma. The occurrence of pigment granules among the cellular debris suggested that the cells were endothelial cells. The corrected distance visual acuity improved from 20/50 to 20/30 in the right eye (+ 0.00/− 1.75/157°) and from 20/60 to 20/30 in the left eye (+ 0.00/− 1.75/33°), with significant improvement in light sensitivity.Conclusion The clinical and ultrastructural findings seem to be an unusual variant of the typical characteristic appearance of a PPCD. This case demonstrates that Triple-DMEK is feasible even in very advanced dystrophic changes of the posterior corneal surface, with good morphological and functional results.
Keywords: Descemet membrane endothelial keratoplasty; DMEK; posterior polymorphous corneal dystrophy; cornea; corneal dystrophy